Analysis of Investment Interest Behavior and Financial Literacy Level of The Poor in Gorontalo Province - Dungga, Meriyana Fransisca; Hinelo, Raflin Fransisca (AIBPM Publisher, 2025)
This paper aims to explore the investment interest behavior and financial literacy level of the poor in Gorontalo Province. This research uses a qualitative approach with a literature study method combined with field interviews as a form of direct observation to strengthen the theoretical study. The results of the author's research show that the investment behavior and interest as well as the level of financial literacy of the poor in Gorontalo Province are still classified as low to moderate. People tend to choose traditional investments that are easy to understand and community-based, but are less able to optimally increase asset value. Low understanding of modern investment products and weak financial management causes people to be trapped in a subsistence economy. Therefore, poverty alleviation efforts need to be accompanied by an increase in financial literacy that is contextual, community-based, and supported by policies and strengthening of local microfinance institutions so that investment can become a tool for long-term economic empowerment